In Vitro Inhibition of Diphtheria Toxin Action by Ammonium Salts and Amines - Kim, K. (1965)
Kim, K. (University of Washington, Seattle), and N. B. Groman. In vitro inhibition of diphtheria toxin action by ammonium salts and amines. J. Bacteriol. 90:1552–1556. 1965.—An inhibitor for diphtheria toxin action on HeLa cells was demonstrated in the growth supernatant fractions of both toxinogenic and nontoxinogenic strains of Corynebacterium diphtheriae and in the Mueller and Miller medium in which these organisms were grown. The inhibitor in the growth supernatant fractions of the nontoxinogenic strain was dialyzable, stable to autoclaving, and stable on storage in the refrigerator for a period of many months, but was destroyed by ashing. When the components of Mueller and Miller medium were analyzed, only the Casamino Acids proved inhibitory. Further study with artificial mixtures of amino acids revealed that glutamine alone inhibited toxin. It was subsequently shown that ammonium salts and the aliphatic amines, glycamine and prolamine, could also function as inhibitors. Histamine and 16 amino acids tested individually were ineffective. The effectiveness of the amines and the ineffectiveness of sodium or potassium ions indicates that there is a specific requirement for inhibition.